A descriptive study of adolescent mothers’ child rearing practices at Western Triangle clinic in Highfield - Munyengeterwa, Brian (Midlands State University, 2018)
The descriptive study of adolescent mothers’ child rearing practices at Western clinic in Highfield, main purpose was to describe the adolescent mothers’ child rearing practices, to identify the common child rearing practices of adolescent mothers, generate new knowledge and to suggest adolescent mothers’ child rearing practices that promotes child’s development. The research was pushed by a growing rise of adolescent mothers, developmental deviations of children born to adolescent mothers and increased risk of child rearing failures of adolescent mothers. A quantitative research approach was used to ascertain a statistical to the study of adolescent mothers’ child rearing practices. A descriptive research design was used to achieve descriptive study of adolescent mothers’ child rearing practices which were various and complex in nature. The research participants were eighty eight adolescent mothers drawn from a population of hundred and twenty adolescent mothers who visited Western Triangle Clinic in Highfield, Krejcie and Morgan’ s sample determination was used to determine the sample size. A simple random sampling technique was used to select participants. Data collected was analyzed by a descriptive statistic approach that depicted graphs, correlation, cross tabulations and SPSS t tests. The research main findings depicted that adolescent mothers lack understanding of child rearing practices. Adolescent mothers show less maternal role, less engagement and harsher punishments on children. The study findings also demonstrated that adolescent mothers physical and emotional withdraw from their children, they also less bath and moderately breastfeed their children. In summation it was found out that most adolescent mother’s child rearing practices indicates increased risks of child rearing failures.